Shear Characteristics of the Interface between Recycled Concrete Aggregates and Various Geosynthetics - Jian-Qi Wu; Lei Li; Guo-Hui Yuan; Bin Wu; Hao Zhang; Li-Jun Zhou (Advances in Civil Engineering)
To investigate the interface shear characteristics between various geosynthetics and recycled concrete aggregate (RCA), 30 large-scale monotonic direct shear tests were conducted. The main work was to analyse the effect of a biaxial polypropylene geogrid, a glass fiber geogrid, a warp-knitted polyester geogrid, a woven geotextile, and geonet on the interface shear properties of RCA. The test results show that adding a biaxial polypropylene geogrid or a geonet to RCA can improve its interface shear strength. The inclusion of glass fiber geogrids, warp-knitted polyester geogrids, and woven geotextiles decrease the interface shear strength of RCA. The reinforcing RCA with geosynthetics can effectively suppress its shear dilation, and the change in internal friction angle is consistent with the change law of the material interface enhancement coefficient. Finally, the aperture size of a geogrid has a significant effect on the mechanical properties of the geogrid-RCA interface. The interface shear strength increases first and then decreases with an increase in the ratio between aperture size and median particle diameter. It is concluded that there is an optimal range of aperture ratio between a geogrid and RCA.